IMPROVING METACOGNITIVE SKILLS THROUGH SCHOOLOGY–BASED BLENDED LEARNING WITH SCIENTIFIC APPROACH - Rona Dea Meistasari; Utiya Azizah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research aimed to describe the feasibility, the improvement of metacognitive skills, learning outcomes, and students' responses to schoology–based blended learning with a scientific approach on the topic of reaction rate. This research used a pre-experimental design, namely One Group Pretest-Postest Design. The research was conducted in class XI IPA 3 SMAN 1 Gurah involving 36 students without the control class. The data were collected through observation, test, and questionnaire. Then, the data were analyzed by calculating the percentage, mean, paired t-test, and N-Gain test. The results showed that 1) Schoology–based blended learning was carried out very well with the criteria of very good for 99.25%; 2) Metacognitive skills which was practiced through Schoology–based blended learning was scored 0.534 meaning that the skills improved well; 3) Student learning outcomes also experienced the completeness for 61% which stated that the use of Schoology–based blended learning was good to improve learning outcomes 4) The students’ response towards the use of Schoology–based blended learning as a learning innovation using technology was considered good with a percentage of 75%. Generally, Schoology–based blended learning was effective in improving students' metacognitive skills.